Mauritius : Challenges of Sustained Growth - Yao, James (International Monetary Fund, 2005)
Mauritius has achieved remarkable success since its independence in 1968. It has one of the highest per capita GDPs in Africa, the economy has diversified from complete dependence on the sugar crop, into textiles, then tourism, and recently information and communication services. This paper examines the factors that have contributed to this impressive growth, including macroeconomic stability, a solid institutional framework, political stability, an efficient administration, a favorable regulatory framework, and a well-developed financial system, and outlines the challenges that remain to ensure continued sustainable growth in Mauritius.